2020
DOI: 10.1038/s41598-020-76298-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral 5-HT5A receptors in 5-HT-induced cardiac sympatho-inhibition in type 1 diabetic rats

Abstract: 5-HT inhibits cardiac sympathetic neurotransmission in normoglycaemic rats, via 5-HT1B, 5-HT1D and 5-HT5A receptor activation. Since type 1 diabetes impairs the cardiac sympathetic innervation leading to cardiopathies, this study aimed to investigate whether the serotonergic influence on cardiac noradrenergic control is altered in type 1 diabetic rats. Diabetes was induced in male Wistar rats by streptozotocin (50 mg/kg, i.p.). Four weeks later, the rats were anaesthetized, pithed and prepared for producing ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The serotonergic system acts as modulator, both potentiating and inhibiting noradrenergic or vagal outflow at cardiac and vascular levels in different experimental models [ 21 , 22 , 23 , 24 , 40 , 41 ]. Furthermore, our group has described the serotonergic inhibitory action of noradrenergic input at mesenteric and renal levels [ 18 , 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serotonergic system acts as modulator, both potentiating and inhibiting noradrenergic or vagal outflow at cardiac and vascular levels in different experimental models [ 21 , 22 , 23 , 24 , 40 , 41 ]. Furthermore, our group has described the serotonergic inhibitory action of noradrenergic input at mesenteric and renal levels [ 18 , 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-HT 1D receptor, at prejunctional locus, has already been described as sympatholytic at the renal level [ 18 ], and at cardiac and vascular levels, in pithed rats as well [ 21 , 40 ] in normoglycaemic animals. In any case, it is worthwhile to mention that short-term diabetic state modifies the serotonergic profile involved in the sympatho-modulation, unmasking peripheral prejunctional 5-HT 1A and 5-HT 5A at vascular and cardiac level, respectively, in pithed rats [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-HT 1 receptors are widely expressed in perivascular and cardiac sympathetic nerve endings; their activation is linked to cardiovascular sympathetic inhibition [48][49][50][51]. Specifically, selective stimulation of 5-HT 1A , 5-HT 1B , and 5-HT 1D receptors produced inhibition of the sympathetic vasopressor outflow in pithed rats [38,52].…”
Section: The 5-ht Receptors Inhibiting the Autonomic Outflowmentioning
confidence: 99%
“…In pithed rats, 5-HT regulates sympathetic cardiac outflow [ 16 , 17 ] and also modulates vagal outflow to the heart via 5-HT 2 and 5-HT 3 receptor activation [ 18 ]. However, experimental T1DM, as well as pharmacological 5-HT modulation by the antagonism of 5-HT 2 receptor, modifies the serotonergic effect on both sympathetic and parasympathetic cardiac discharge [ 19 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, our group has demonstrated that, in naïve animals, the chronic treatment with a SSRI (fluoxetine) modifies the serotonergic modulation of vagal bradycardia, exerting an inhibitory action of the vagal cardiac input due to activation of prejunctional 5-HT 1D receptors [ 25 ].…”
Section: Introductionmentioning
confidence: 99%